Pemberdayaan Kader Pemberian Makanan Pendamping ASI (MPASI) Premium dalam Upaya Pencegahan Stunting: Empowerment of Cadres for Providing Premium Complementary Feeding (MPASI) in an effort to Prevent Stunting - Rahmawati, Wenny; Retnaningrum, Dwi Norma (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Stunting is a health problem that is the main focus of all groups. One of the efforts to prevent stunting is by providing balanced nutritional complementary food for toddlers. MPASI Premium is MPASIwhich comes from family food, not ready-to-eat food or certain factory products. Giving premium MPASI is more recommended because it will make it easier for babies to get used to family food which will be consumed at a higher age.Stunting incidents in Sukomulyo Village reached 14.5% or 128 toddlers of the total number of stunting incidents in Pujon District. The results of a survey conducted in June 2022 with village midwives and several cadres stated that 83% of mothers chose to provide instant complementary food (MPASI), because it was more practical and babies ate more voraciously with instant food. Mother's knowledge of essential nutrients in solids is also lacking. The purpose of this service activity is to increase cadre knowledge regarding Premium MPASI. The solutions offered include empowerment, training and mentoring of Posyandu toddler cadres in Sukomulyo village regarding the creation of a Premium MPASI menu variant. The method used is counseling and training in making Premium MPASI products. The results of the activity formed 10 MPASI Premium Companion cadres and there was an increase in the knowledge of the cadres regarding stunting prevention and Premium MPASI.